Analisis Postur Kerja Operator Mesin Bubut di PT. X - Rohmana, Rohmana; Setiani, Alisha (Metris: Jurnal Sains dan Teknologi, 2019)
PT. X is one of the aerospace companies in Asia that has core competencies in the design and development of airplanes. The manufacture of aircraft certainly requires aircraft aids made by Machining tools. In this section there are many machine operators, of course, require interaction between humans and machines. However, there are some operators that still use conventional lathes. The research is analyzing the work posture of conventional lathe operators using the RULA (Rapid Upper Limb Assessment) method. The initial observation was to disseminate the Nordic Body Map questionnaire to 2 lathe operators with the same task, to find out complaints that occurred during or finished working. The results of calculations using the Ergo Fellow software and manual calculations produce the same score. Assessment of work posture on the lathe operator PT. Indonesian Aerospace obtained a RULA score of 6, Action Level 3, indicating that it has a moderate level of risk and action is needed in the near future.